2011
DOI: 10.1002/pat.2042
|View full text |Cite
|
Sign up to set email alerts
|

A main‐chain phosphorus‐containing poly(trimethylene terephthalate) copolyester: synthesis, characterization, and flame retardance

Abstract: In order to improve the flame retardancy of the semi‐biobased polyester, poly(trimethylene terephthalate) (PTT), bis‐4‐carboxyphenyl phenyl phosphine oxide (BCPPO) was used as a third monomer to synthesize a novel main‐chain phosphorus‐containing copolyester, poly(trimethylene terephthalate‐co‐BCPPO)s (PTTBP), through melt polycondensation. Phosphorus analysis of the resulting polymers suggests that BCPPO has been introduced to PTT chain successfully. 1H and 31P nuclear magnetic resonance spectra further confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The onset weight-loss temperature shows the same trend as was observed under nitrogen testing; the temperature increased from 337.1 • C for neat PTT to 375.8 • C for PTTEP30, consistent with increased cabonization in the presence of phosphorus. The char residue increases from 0.4% for neat PTT to 13.2% for PTTEP30, consistent with the weight-loss results presented above, but differing favorably from previously reported phosphorus-containing systems [3,4]. It is probably that the present system produces less volatile phosphorus compounds, affording it with significant benefits when compared to other phosphorus-modified polyesters.…”
Section: Tgasupporting
confidence: 89%
See 3 more Smart Citations
“…The onset weight-loss temperature shows the same trend as was observed under nitrogen testing; the temperature increased from 337.1 • C for neat PTT to 375.8 • C for PTTEP30, consistent with increased cabonization in the presence of phosphorus. The char residue increases from 0.4% for neat PTT to 13.2% for PTTEP30, consistent with the weight-loss results presented above, but differing favorably from previously reported phosphorus-containing systems [3,4]. It is probably that the present system produces less volatile phosphorus compounds, affording it with significant benefits when compared to other phosphorus-modified polyesters.…”
Section: Tgasupporting
confidence: 89%
“…1), together with melting point analysis. The 1 H NMR peaks at 7.0-8.3 (a) ppm is assigned to aryl groups of DOPO-HQ-HE; the peaks occurring at 4.0 (b), 3.7 (c), 3.6 (d), and 2.9 (e) ppm belong to methylene groups of DOPO-HQ-HE; the peaks at 4.5 (g) and 4.8 (f) ppm are attributed to hydroxyl groups. The melting point of DOPO-HQ-HE obtained from DSC is 153-156 • C, which is the same as reported in the literature (157-158 • C) [24], which further indicates the successful synthesis of DOPO-HQ-HE.…”
Section: Synthesis Of Dopo-hq-hementioning
confidence: 98%
See 2 more Smart Citations
“…They examined the possibility of using bromine-containing terephthalic acids as monomers for the preparation of re-resistance bers. 12 Bis(4-carboxyphenyl)phenyl phosphine oxide (BCPPO) is a highly efficient ame retardant containing triaryl phosphine oxide (TPO) and dicarboxy functional groups, which has been used as a third monomer to prepare many inherently ameretardant polymers, such as poly(trimethylene terephthalate), 13 poly(ethylene terephthalate), 14,15 polyarylate, 16 polyamide 66, 17 soluble aromatic copolyamides 18 etc. From these literatures, it can be found that the copolymers exhibited improved ame retardance, hydrolytic stability and thermal stability, when BCPPO was incorporated into their main chains.…”
Section: Introductionmentioning
confidence: 99%